Developing Poster for Teaching Vocabulary to Young Learners - Misa Feronika; Sumarni; Wardah (Universitas Islam Negeri Palopo, 2025)
This study aimed to develop the posters designed for teaching vocabulary to young learners, specifically within the context of TK Primanda UNTAN in Pontianak. This study utilized the ADDIE development model, focusing on three phases: analysis, design, and development. Data were collected through an interview and an assessment rubric to evaluate the final product. Analysis of the data was conducted using Aiken's V. According to the teacher's assessment rubric, the poster received a score of 0.96, indicating that it is feasible, valid, and acceptable for use in teaching vocabulary to young learners. This research contributes valuable insights into the effective design and development of instructional materials for enhancing vocabulary acquisition in early childhood education.